Investment and sustainability: CSR, SDGs and the ESG Score in Indonesia - Iqbal Lhutfi; Unti Ludigdo; Mohamad Khoiru Rusydi; Zaki Baridwan (Cogent Business & Management, 2024)
This study examines how Corporate Social Responsibility (CSR) disclosure and Sustainable Development Goals (SDGs) affect investment decisions mediated by Environmental, Social, and Governance (ESG) scores. Structural Equation Modeling (SEM) was used to test the hypotheses of this study using the SmartPLS 3.0 programme. Testing the router model is done using algorithmic techniques, and the inner model is tested by bootstrapping and model testing using goodness of fit. By analysing data from 79 companies listed on the Indonesia Stock Exchange (IDX), we found that CSR and SDGs disclosures positively affect ESG scores. ESG scores also positively affect investment decisions as measured by earnings per share. The findings of this test indicate that ESG scores mediate the relationship between CSR disclosure and earnings per share in a statistically significant way. However, the mediation of ESG score on the relationship between SDGs disclosure and earnings per share was not found to have a significant effect.
Keywords: G11; M14; Q01; Q56; 650; CSR disclosure; SDGs disclosure; ESG score; investment decision